Biomaterial‐Based Approaches to Address Vein Graft and Hemodialysis Access Failures. Issue 23 (27th September 2016) - Boire, Timothy C.; Balikov, Daniel A.; Lee, Yunki; Guth, Christy M.; Cheung‐Flynn, Joyce; Sung, Hak‐Joon
Abstract : Veins used as grafts in heart bypass or as access points in hemodialysis exhibit high failure rates, thereby causing significant morbidity and mortality for patients. Interventional or revisional surgeries required to correct these failures have been met with limited success and exorbitant costs, particularly for the US Centers for Medicare & Medicaid Services. Vein stenosis or occlusion leading to failure is primarily the result of neointimal hyperplasia. Systemic therapies have achieved little long‐term success, indicating the need for more localized, sustained, biomaterial‐based solutions. Numerous studies have demonstrated the ability of external stents to reduce neointimal hyperplasia. However, successful results from animal models have failed to translate to the clinic thus far, and no external stent is currently approved for use in the US to prevent vein graft or hemodialysis access failures. This review discusses current progress in the field, design considerations, and future perspectives for biomaterial‐based external stents. More comparative studies iteratively modulating biomaterial and biomaterial‐drug approaches are critical in addressing mechanistic knowledge gaps associated with external stent application to the arteriovenous environment. Addressing these gaps will ultimately lead to more viable solutions that prevent vein graft and hemodialysis access failures. Abstract : External stents provide a promising means to prevent vein graft and hemodialysis access failures . Its ability to do this depends on the material and scaffold design chosen. Physicochemical properties (e.g., chemistry, molecular weight) and scaffold geometry (e.g., diameter, length, pore size and interconnectivity) govern the stent properties (e.g., biodegradation time, mechanical properties) and, ultimately, the biological response that it elicits.